Consolidating Management Accounting and Economic Security System in a Business Enterprise: A Conceptual Framework - О. PYLYPENKO (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2021)
The effectiveness of business management in precarious economic conditions can decrease due to the lack of a well-established economic security system and relevant accounting information that is also an object of special protection. Accounting and security functions in a business enterprise have organic links that need to be shown in organizational measures aimed at elaborating the accounting support for the economic security system in way to achieve its integrity and efficiency.